Identifikasi Pendidikan sebagai Suatu Sistem untuk Kemajuan Pendidikan Menuju Indonesia Emas 2045 - Habsy, Bakhrudin All; Rahayu, Farida Muji; Mareta, Riska Dwi; Apriliani, Imaniar (Lembaga Yasin AlSys, 2024)
Education is said to be a system because there is a function and also components of education that are interconnected and there is a relationship between each other to achieve the expected goals. This research aims to find out how the education process can be said to be a system, therefore this research focuses on aspects that support the topic of the task. The research was conducted using a qualitative method literature study. The results of this study include: (1) Education Curriculum, (2) Evaluation and Assessment (3) The Meaning of Teaching and Learning (4) Student and Teacher Duties (5) Policies and Regulations (6) Education Management in Schools.